Ergodicity of Stochastic Burgers' System with Dissipative Term. (31st December 2013) - Zhou, Guoli; Guo, Boling; Huang, Daiwen; Han, Yongqian
Abstract : A 2-dimensional stochastic Burgers equation with dissipative term perturbed by Wiener noise is considered. The aim is to prove the well-posedness, existence, and uniqueness of invariant measure as well as strong law of large numbers and convergence to equilibrium.